Development of a recombinase polymerase amplification assay with lateral flow dipstick (RPA-LFD) for rapid detection of Shigella spp. and enteroinvasive Escherichia coli - Bian, Zheng; Liu, Wenbo; Jin, Junhua; Hao, Yanling; Jiang, Linshu; Xie, Yuanhong; Zhang, Hongxing (PloS one, 2022)
Shigella spp. and enteroinvasive Escherichia coli (EIEC) are widely distributed and can cause serious food-borne diseases for humans such as dysentery. Therefore, an efficient detection platform is needed to detect Shigella and EIEC quickly and sensitively. In this study, a method called recombinase polymerase amplification combined with lateral flow dipstick (RPA-LFD) was developed for rapid detection of Shigella and EIEC. RPA primers and LFD detection probes were designed for their shared virulence gene ipaH . Primers and probes were screened, and the primer concentration, and reaction time and temperature were optimized. According to the optimization results, the RPA reaction should be performed at 39°C, and when combined with LFD, it takes less than 25 min for detection with the naked eye. The developed RPA-LFD method specifically targets gene ipaH and has no cross-reactivity with other common food-borne pathogens. In addition, the minimum detection limit of RPA-LFD is 1.29×10 2 copies/μL. The detection of food sample showed that the RPA-LFD method was also verified for the detection of actual samples.